The juridical voice of literature: a perspective on literature's entanglement with normativity - Becker, Katrin; Justus Liebig University Giessen (My University, 2017)
Based on the logic of the Lacanian mirror paradigm, Pierre Legendre claims that every culture needs to create a metaphysical entity of Reference, for the sake of the legitimacy and validity of its normative system. This entity disguises the abyss at the core of culture and legitimates it by staging itself as its origin. As such, the Reference not only authenticates individual and cultural subjectivity, but also becomes the foundation of law. Given that Legendre attributes a fundamental role to aesthetics in the creation of this entity, my essay will identify the role of literature in this respect, arguing that, on the one hand, literary texts help confirming the readers attachment to a specific order of Reference, i.e. of normativity and imagery. On the other hand, my essay claims that literature also has the capacity to reflect on the basis of cultural normativity and to unveil the contingency of normative truths. This results from what I call the cultural structures of testimony. Thus literature unleashes emancipatory forces with regard to a culture s normative system. The essay tests this hypothesis by analysing E.T.A. Hoffmann s The Sandman, a narrative that because of its play with the categories of fiction and reality is particularly salient.
Keywords: aesthetic basis of culture; Hoffmann; Legendre; normativity; testimony; ddc:800